Influence of Codoping on the Optical Properties of ZnO Thin Films Synthesized on Glass Substrate by Chemical Bath Deposition Method - G. Shanmuganathan; I. B. Shameem Banu (Advances in Condensed Matter Physics)
Fe and K simultaneously doped ZnO thin films Zn0.99 K0.01 (Fe)x O (x=1, 2, 3, and 4%) were synthesized by chemical bath deposition method. The XRD investigation reveals that all the doped ZnO thin films are in hexagonal wurtzite crystal structure without impurity phases. With increase in Fe concentration, the growth of thin films along c axis is evident from the XRD which indicates the increase in intensity along (002) direction. The same is visible from the surface morphology which shows the formation of hexagonal structure for higher Fe concentration. The topography shows gradual variation with Fe incorporation. The optical energy band gap obtained from the transmittance spectrum decreases from 3.42 to 3.06 eV with increase in Fe concentration indicating the red shift and this trend is consistent with the earlier experimental results. The UV emission is centered around 3.59 eV. The optical constants such as refractive index, extinction coefficient, and absorption coefficient which are essential for the optoelectronic applications were also determined.